Enhancing Optical Forces on Fluorescent Up‐Converting Nanoparticles by Surface Charge Tailoring. Issue 13 (1st December 2014) - Rodríguez‐Rodríguez, Héctor; Rodríguez Sevilla, Paloma; Martín Rodríguez, Emma; Ortgies, Dirk H.; Pedroni, Marco; Speghini, Adolfo; Bettinelli, Marco; Jaque, Daniel; Haro‐González, Patricia
<x xml:space="preserve">Abstract</x> 3D remote control of multifunctional fluorescent up‐converting nanoparticles (UCNPs) using optical forces is being required for a great variety of applications including single‐particle spectroscopy, single‐particle intracellular sensing, controlled and selective light‐activated drug delivery and light control at the nanoscale. Most of these potential applications find a serious limitation in the reduced value of optical forces (tens of fN) acting on these nanoparticles, due to their reduced dimensions (typically around 10 nm). In this work, this limitation is faced and it is demonstrated that the magnitude of optical forces acting on UCNPs can be enhanced by more than one order of magnitude by a controlled modification of the particle/medium interface. In particular, substitution of cationic species at the surface by other species with higher mobility could lead to UCNPs trapping with constants comparable to those of spherical metallic nanoparticles.